2021
DOI: 10.1002/er.6892
|View full text |Cite
|
Sign up to set email alerts
|

An accurate numerical approach for studying perovskite solar cells

Abstract: Summary This work presents different numerical methods that are used for the first time in solving Perovskite solar cells (PSCs). Classical differential quadrature, sinc, and discrete singular convolution (Regularized Shannon and Delta Lagrange kernels) methods are employed for studying this problem. The governing equations are derived based on Poisson's and continuity equations. The different quadrature techniques are introduced to convert the system of nonlinear partial differential equations to nonlinear al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
(138 reference statements)
0
15
0
Order By: Relevance
“…It is important to perform simulation of the design and structures of the device before actually doing the experiments. It can influence the cost of several sets of experiments 42‐47 . Solar Cell Capacitance Simulator (SCAPS) is a one‐dimension simulation tool to simulate the effects of different layers in PSCs 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to perform simulation of the design and structures of the device before actually doing the experiments. It can influence the cost of several sets of experiments 42‐47 . Solar Cell Capacitance Simulator (SCAPS) is a one‐dimension simulation tool to simulate the effects of different layers in PSCs 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Cu-based device (0. sets of experiments. [42][43][44][45][46][47] Solar Cell Capacitance Simulator (SCAPS) is a one-dimension simulation tool to simulate the effects of different layers in PSCs. 48 In general, SCAPS is used for simulating planar structures.…”
Section: Samplementioning
confidence: 99%
“…Then the iterative method is applied to solve the problem of nonlinearity. 44,45,53 The iterative method depends on solving the system as linear. Then we solved it as nonlinear by applying the condition convergence such as follows 44,45,53 :…”
Section: Block-marching Methods With Dq Discretization (Bmr)mentioning
confidence: 99%
“…Narendhiran et al 43 demonstrated that PVDF-HFP additive added into the perovskite precursors is beneficial for improving both the device performance and stability of PSC. Ragb et al 44 proved that differential quadrature (DQ) technique with different shape functions achieves accurate results with fewer grid points and without exerting great efforts. They are the first used techniques to study the primary PSC and the effect of interface materials on PSC efficiency and charge carriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation